Happiness is a choice - Kaufman, Barry Neil. (New York : Ballantine Books, 1994)
Kaufman's Option Institute focuses on six shortcuts to happiness starting with self-acceptance.
Includes bibliographical references and index.
Adult
Keywords: Happiness; Self-help techniques; Applied psychology; Happiness; Self-acceptance.